Probiotic foods in health and disease - Nair, G. Balakrish; Takeda, Yoshifumi , 1935- (Science Publishers ; Marketed and distributed by, CRC Press, 2011)
"Probiotic Foods in Health and Disease" compiled by leading experts is a blend of fundamental and applied research related to the use of these important organisms in enhancement of human health. The book aims at covering all aspects of the intestinal microflora and offers a comprehensive review of the broad array of effects that can be attributed to probiotic usage. While the thrust remains the latest and most exciting findings in the field of gut health, it also opens a window to the possible role of probiotics beyond the gut such as oral health care, allergic disorders and women's health. The book also reviews pertinent legislation regulating the use of probiotics across the globe with special emphasis on Japan, a country which pioneered the establishment of a regulatory framework for functional foods, or foods that promote a health benefit besides providing basic nutrition. Each chapter offers a insight of the topic, reviews current research and discusses future direction. Most of the references that have been cited in the book chapters are recent, exploit modern methodologies, good controls and rational explanations for the probiotic benefits"-- Provided by publisher.